ETR 300: Clothing (CLO) / Mohd Fauzi Othman … [et al.] - Othman, Mohd Fauzi; Osman, Mohd KhairilNaim; Mohmad Azmi, Nurul Hafis; Omar Hamzah Zamhari, Zulfaddhly; Ahmad Wahid, Amirul Idzanney (2002)
Creative Design Enterprise is a partnership organization that provide cloth printing services to local clients and also sell various of brand' cloth. Creative Design Enterprise is kind of partnership that contains of five creative youth. The partnership will compete with other company in textile industry, which nowadays is one of the most popular industries. Creative Design Enterprise is always aware about the demand of fashion among Shah Alam's residents and therefore, all the partners had decided to set up a partnership that can provide cloth printing especially for the students and worker's organization. Creative Design Enterprise will commence the business in Shah Alam where it is situated at No. 6 Jalan Timun E 24/E,40200 Shah Alam, Selangor. Our partnership business will be fully started on 1st January 2008 with total contribution from each partner is RM 10,000. Each partner will bring RM5,000 for in the second year. Furthermore, all the partners had decided to apply for the bank loan amount RM50.000 to make sure the business be more effective and efficient. All the partners have their own qualifications. Hence, our company is different than other companies because our management is more comprehensive. Our role is to satisfy all the consumer's need and want with give our best services to them. The consumers also can submit their own design to us so we can create it as well as what they want. Factors of influencing choice of the business are such as near the UiTM area. Some students live outside the college such as at section 24. Our market is among the UiTM student and the school students. The kindergarten is also includes in our target market. The business potential is good because the market is wide and big. Hence, the business can be expanded widely. Furthermore, most students need to wear shirt especially for their class and certain event such as sport and co-curriculum activities.